Correlates of hepatitis C virus seropositivity in prison inmates: a meta-analysis. Issue 4 (13th March 2008) - Vescio, M F; Longo, B; Babudieri, S; Starnini, G; Carbonara, S; Rezza, G; Monarca, R
Abstract : Background: The prevalence of infection with hepatitis C virus (HCV) is higher among prison inmates compared with the general population because of the high proportion of injecting drug users (IDU). Methods: A meta-analysis of studies on HCV infection in the correctional system was performed. The main objective was to analyse risk factors for HCV infection and to assess HCV seroprevalence and incidence in prison. Results: Thirty studies were included in the meta-analysis on HCV prevalence. IDU were approximately 24 times more likely than non-IDU to be HCV positive. The odds ratio of being HCV positive was three times higher for inmates exposed to tattooing than those not exposed. The odds ratio among women was 1.44 compared with men. Conclusions: The differences in HCV seroprevalence among studies can largely be explained by differences in the proportion of inmates who are IDU and partly by differences in seroprevalence among IDU in the community. Tattooing and female gender were also associated with HCV positivity. These findings should be taken into account when planning prevention activities in prisons.